Factors Affecting Work Stress Among Employees At The Muara Pinang Inpatient Health Centre In Empat Lawang District, South Sumatra Province - Sapitri, Wulan; Anggriani , Ida; Kurniawan , Kimas (Journal of Accounting and Management, 2025)
The purpose of this study is to find out the Factors That Affect Work Stress of Employees of the Muara Pinang Inpatient Health Center, Empat Lawang Regency, South Sumatra Province. This study uses a quantitative method. Based on the results of the analysis, the regression equation was obtained: Y = -1.219 + 0.002X₁ + 0.164X₂ + 0.732X₃. The results of the partial test (t-test) showed that the Individual Factor (X₁) had no significant effect on Work Stress with a t-count value = 0.049 < t-table = 1.974 and a significance of 0.961 > 0.05. Organizational Factor (X₂) had a positive and significant effect on Work Stress with a t-count value = 3,294 > t-table = 1.974 and significance 0.001 < 0.05. Environmental Factor (X₃) is the most dominant variable with t-calculated values = 14,622 > t-table = 1.974 and significance 0.000 < 0.05. Simultaneously, the results of the F test showed that the three variables had a significant effect on Work Stress with a value of F-calculation = 83,918 > F-table = 2.66 and a significance of 0.000 < 0.05. The value of the determination coefficient (R²) = 0.603 showed that Individual Factors, Organizational Factors, and Environmental Factors were able to explain 60.3% of the variation in Work Stress, while the remaining 39.7% were explained by other variables outside of this study. Thus, it can be concluded that the increase in employee Work Stress is more influenced by organizational conditions and work environment than individual factors.